2010
DOI: 10.2215/cjn.03340509
|View full text |Cite
|
Sign up to set email alerts
|

Role of Residual Kidney Function and Convective Volume on Change in β2-Microglobulin Levels in Hemodiafiltration Patients

Abstract: Background and objectives: Removal of ␤ 2 -microglobulin (␤2M) can be increased by adding convective transport to hemodialysis (HD). The aim of this study was to investigate the change in ␤2M levels after 6-mo treatment with hemodiafiltration (HDF) and to evaluate the role of residual kidney function (RKF) and the amount of convective volume with this change.Design, setting, participants, & measurements: Predialysis serum ␤2M levels were evaluated in 230 patients with and 176 patients without RKF from the CONv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 28 publications
2
42
1
3
Order By: Relevance
“…In a previous analysis of the CONTRAST study, we showed that the effect of online hemodiafiltration on b-2-microglobulin levels was especially present in patients without residual kidney function. 7 However, neither residual kidney function, nor an analysis of other predefined subgroups, such as primary kidney disease, age, co-morbidity, and sex modified the effect of treatment in our study. Because the CONTRAST study was not powered to detect differences between low-flux hemodialysis and hemodiafiltration on outcome across subgroups, our "null" results in subgroup analyses do no exclude the presence of such a relation.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In a previous analysis of the CONTRAST study, we showed that the effect of online hemodiafiltration on b-2-microglobulin levels was especially present in patients without residual kidney function. 7 However, neither residual kidney function, nor an analysis of other predefined subgroups, such as primary kidney disease, age, co-morbidity, and sex modified the effect of treatment in our study. Because the CONTRAST study was not powered to detect differences between low-flux hemodialysis and hemodiafiltration on outcome across subgroups, our "null" results in subgroup analyses do no exclude the presence of such a relation.…”
Section: Discussioncontrasting
confidence: 60%
“…With modern online hemodiafiltration equipment, high convection and substitution volumes can be reached safely, 3 resulting in markedly enhanced removal of middle molecular mass substances. [4][5][6][7] Several nonrandomized observational studies suggested a survival benefit in patients who are treated with online hemodiafiltration. [8][9][10][11] However, small randomized studies failed to show a difference between online hemodiafiltration and standard hemodialysis (as summarized by van der Weerd et al 12 ).…”
mentioning
confidence: 99%
“…Apart from phosphate and anemia control, our data showed a strong relation between RRF and ␤2M level, as previously reported (6,7,49), and suggested that even a GFR Ͻ1.65 ml/min contributes to ␤2M removal. Notably, we have recently shown that RRF appears to be more important for ␤2M removal than intensifying dialysis treatment with online hemodiafiltration (50). Not surprising, but of potential clinical interest, is the finding that intradialytic weight loss was much lower in patients with urinary output as compared with anuric patients.…”
Section: Discussionmentioning
confidence: 98%
“…17,18,24 These benefits are thought to be mediated by continuous and efficient clearance of middle molecules and protein-bound solutes, better fluid management, more endogenous vitamin D and erythropoietin production, and less inflammation. [25][26][27][28] Decline and loss of RKF are associated with higher mortality, 18 and the frequency of HD may contribute to loss of RKF. In our study, we found that patients initiated on a frequent HD regimen ($4 times per week for at least 45 continuous days) had a higher mortality than patients initiated on an incremental or conventional regimen.…”
Section: Discussionmentioning
confidence: 99%